Premia and Discount of Rice Characteristics: The Case of Retail Market in Bogor-Indonesia - Harianto Harianto; Nunung Kusnadi; Layyinatul Kholiqoh (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Rice marketing in Indonesia has undergone significant changes, especially at the retailer level. Rice provided by retailers is increasingly diverse, both in terms of variation and quality. This study is aimed at analyzing the implicit value of various characteristics that are generally used as a reference when consumers buy rice at retailers. The study employed a hedonic price model, which was originally introduced by Lancaster. The data used are primary data from the survey of various types of rice sold by retailers in various locations in urban area of Bogor. The survey was conducted in March 2018. The results showed that the content of rice fragments or minute kernels and off-color rice can discount the price of rice. The estimation results of the model also showed that the length characteristic had a negative influence on the price of rice. Rice producers and traders have the opportunity to increase the price of rice they sold by reducing contents of the minute kernel and off-color rice that can be visually observed by consumers when making the choice of rice to buy.Keywords: consumer preference, implicit price, quality attributes, retail market